Combining spacings and plant populations in single and double cropping - de Oliveira, Francisco José (Pesquisa Agropecuaria Brasileira, 1993)
Under rain season conditions in Parnamirim and Serra Talhada counties, in Pernambuco, Brazil, the yields of three cowpea (Vigna unguiculata L. (Walp) cultivars and one corn (Zea mays L.) cultivar were studied when planted in simple and double cropping patterns. The grain yield of the cowpea decreased with the reduction of plant density in double cropping. On the other hand, the grain yield of corn plants in the double cropping was superior to that of the simple one, with plant densities from 25,000 to 45,000 plants per hectare, with an increase ranging from 5% to 86% in relation to its monocrop. Due to the interspecific competition, the reduction in yield of corn under simple cropping was significant with plant densities of 80,000, 100.000 and 120,000 plants per hectare. Other data concerning land efficient use (UET) and population and competition coefficients were also estimated. Generally, the hydric factor, edafic aspects and planting density of leguminosae versus gramineae interacted in combining arrangements of the two crops.